DS-MAC: An energy efficient demand sleep MAC protocol with low latency for wireless sensor networks. (December 2015) - Wang, Guijuan; Yu, Jiguo; Yu, Dongxiao; Yu, Haitao; Feng, Li; liu, Pan
Abstract: Duty cycling mechanism has been widely used to conserve energy that consumed by idle listening in wireless sensor networks, while fixed duty cycling introduces transmission latency in packet delivery. End to end latency is one of the most significant factors of packets loss in wireless sensor nodes, and many techniques have been proposed based on listening adaptively to reduce delay, which are mainly designed for light traffic loads. In this paper, we propose a novel asynchronous duty cycling MAC protocol, called demand sleep MAC (DS-MAC) that allows nodes to adjust their sleep time adaptively according to the amount of the received data packets in order to efficient and effective communication in the dynamic traffic load. DS-MAC protocol attempts to transmit a series of short token packets to wake up the receiver, which avoids the overhearing problem. Nodes in DS-MAC put the prediction field into ACK packets, which decreases the waiting delay of source node. Comprehensive simulation shows that when there are variable flows, such as broadcast traffic or transmissions from hidden nodes, DS-MAC significantly decreases waiting delay and energy consumption.